Moral deliberation and ad hominem fallacies - Leibowitz, Uri D. (Brill, 2015)
Many of us read Peter Singer’s work on our obligations to those in desperate need with our students. Famously, Singer argues that we have a moral obligation to give a significant portion of our assets to famine relief. If my own experience is not atypical, it is quite common for students, upon grasping the implications of Singer’s argument, to ask whether Singer gives to famine relief. In response it might be tempting to remind students of the (so called) ad hominem fallacy of attacking the person advancing an argument rather than the argument itself. In this paper I argue that the “ad hominem reply” to students’ request for information about Singer is misguided. First I show that biographical facts about the person advancing an argument can constitute indirect evidence for the soundness/unsoundness of the argument. Second, I argue that such facts are relevant because they may reveal that one can discard the argument without thereby incurring moral responsibility for failing to act on its conclusion even if the argument is sound.